An Ethnographic Study of the Bugis Community: Deconstructing Multicultural Islamic Educational Values in Bugis Society - Muhammad Tang; Muhammad Rizal Masdul; Hartina; Muhammad Ilham Hidayat (Bulletin of Community Engagement, 2025)
The objective of this study is to analyze, interpret, identify, and describe the values of Islamic education from a multicultural perspective as embedded in the cultural practices of the Bugis community. Employing a qualitative method with a combined autoethnographic and realist ethnographic approach, the research utilized in-depth interviews, participant observation, and document analysis as the primary data collection techniques. Data were examined through domain, taxonomic, and componential analyses, culminating in the formulation of key cultural values. The findings reveal seven core values within Bugis culture that can be adapted into a multicultural Islamic educational framework: (1) mutual respect and reverence, (2) compassion, (3) constructive admonition, (4) cooperation, (5) mutual protection, (6) recognition of human rights, and (7) cleanliness. The implications of this study suggest that these culturally rooted values can contribute significantly to the development of multicultural Islamic education in Indonesia. this research contributes to the preservation and academic recognition of Bugis cultural heritage by positioning it as a dynamic source of ethical and educational values, thereby bridging local culture with national and global discourses on multicultural and Islamic education.